Interventionism and Over-Time Causal Analysis in Social Sciences. Issue 1 (January 2022) - Wu, Tung-Ying
The interventionist theory of causation has been advertised as an empirically informed and more nuanced approach to causality than the competing theories. However, previous literature has not yet analyzed the regression discontinuity (hereafter, RD) and the difference-in-differences (hereafter, DD) within an interventionist framework. In this paper, I point out several drawbacks of using the interventionist methodology for justifying the DD and RD designs. Nevertheless, I argue that the first step toward enhancing our understanding of the DD and RD designs from an interventionist perspective is to take advantage of the assumptions of common trend and continuity.